Efeito de um programa de treinamento de 23 semanas nas variáveis antropométricas e neuromusculares em jovens nadadores - Leite, Richard Diego (2007)
The aim of this study was to evaluate the influence of a training program on anthropometric and neuromuscular variables in young swimming athletes. 16 athletes were accomplished, nine boys and seven girls, with a mean age of 14.06 1.22 years old. Training was divided into four mesocycles: T1=general endurance; T2=specific endurance; T3=competitive; T4=taper, with total duration of 23 weeks. The anthropometric variables analyzed were: body mass (Kg), height (m), BMI (Kg/m2), fat-free mass (kg) and fat mass (kg). Neuromuscular variables analyzed were: vertical jump (cm), medicine ball throw (m), bench press (kg) and leg press (Kg) maximal strength. Friedmann and Wilcoxon tests were used, with p< 0.05. In male and female gender height and body mass were superior in T4 compared to other phases (T1, T2 and T3). In upper body power a higher value was observed in T4 compared to other phases for the boys; in female T3 was superior to T1 and T2. This behavior was also observed in bench press for the girls. Therefore, training associated to physical development induced modifications in athletes’ morphology. Finally, training seems to exert influence on lower body maximal strength differently, along with the training phase.